Upaya Peningkatan Keselamatan Pasien dengan Pelaksanaan Manajemen Risiko di Unit Rawat Inap - Hernawati, Lestari; Rahman, La Ode Abdul; Hariyati, Rr. Tutik Sri; Wildani, Andi Amalia; Erwin, Erwin (Journal of Telenursing (JOTING), 2023)
This study aims to describe the implementation of planned changes in an effort to improve patient safety through optimizing monitoring and evaluation of the implementation of risk management countermeasures in inpatient rooms. The method used is to use a problem solving cycle approach which includes identifying problems, analysis and diagnosis, designing solutions, implementation and evaluation. The assessment was carried out by means of structured interviews, observation, and distributing questionnaires. Implementation of planned changes using Kurt Lewin's change model, namely unfreezing, movement and refreezing. The results of problem identification showed that the implementation of risk management in the inpatient unit was not optimal, so innovation was needed to motivate staff to implement patient safety by distributing online flyers and creating an instrument to monitor the implementation of risk management. In conclusion, monitoring using good monitoring instruments and distributing online flyers can increase nurses' understanding of implementing risk management so that patient safety can be realized. Keywords: Patient Safety, Risk Management, Service Quality Improvement, Monitoring System